0.5(3g-2)=g

Simple and best practice solution for 0.5(3g-2)=g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.5(3g-2)=g equation:


Simplifying
0.5(3g + -2) = g

Reorder the terms:
0.5(-2 + 3g) = g
(-2 * 0.5 + 3g * 0.5) = g
(-1 + 1.5g) = g

Solving
-1 + 1.5g = g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-1g' to each side of the equation.
-1 + 1.5g + -1g = g + -1g

Combine like terms: 1.5g + -1g = 0.5g
-1 + 0.5g = g + -1g

Combine like terms: g + -1g = 0
-1 + 0.5g = 0

Add '1' to each side of the equation.
-1 + 1 + 0.5g = 0 + 1

Combine like terms: -1 + 1 = 0
0 + 0.5g = 0 + 1
0.5g = 0 + 1

Combine like terms: 0 + 1 = 1
0.5g = 1

Divide each side by '0.5'.
g = 2

Simplifying
g = 2

See similar equations:

| 3x+4y=35 | | d+25=b | | -3h+12-4h=-7h-16 | | -1=(x/4)-3 | | 2(-8+8x)+5x=-100 | | 3x+49=3 | | 3x+3y=20 | | 8c=7*16 | | 3x+2+2x=x+16 | | 2a+3a+4=5a-18 | | x-1=2x-2 | | 315=-5(1-8v) | | 3t-t=-22 | | 458=6x+308 | | -8(-2x-5)-4x=88 | | -34=-4(x+4)-5x | | y=(8-6k)x | | 3y-9x=21 | | 3a=2*12 | | 9(x+8)+6=4(x+7) | | -3x+4+3x-3=5 | | 1.09=1.3h | | 9c=7*54 | | 6x-2+7x=180 | | 5x-8+3x=24 | | (2x+7)(x+5)= | | 8=4x+4-3x | | 8(z-6)=-16 | | 2212=-14c | | 14d=126*3 | | -8(4v+5)=-104 | | 3[4y+2(x-3)+2y-4]= |

Equations solver categories